Implementasi Model Scrum pada Sistem Informasi Seleksi Masuk Mahasiswa Politeknik Pariwisata Palembang - Usman Ependi (Politeknik Harapan Bersama, 2018)
SCRUM is one of the agile development that put the speed in the process forward. In the development process SCRUM embraces three main rules: product owner (PO), SCRUM master (SM), and cross functional supported by five backlog refinement, sprint planning, daily meeting, reviews, and sprint retrospective activities. SCRUM ability is very suitable with the conditions that occur in Poltekpar Palembang which requires student enrollment selection information system to fulfill the quota of admission of new students in a short time. Therefore, this research, conducted to develop modified SCRUM SMM information system with the requirement gathering stage, product backlog, sprint backlog, sprint, IS development, and delivery-implementation. The final result of this research is SMM Information System of Poltekpar Palembang that can really fulfill user requirement which can be seen from SMM information system product backlog. SMM Information System of Poltekpar Palembang also has a feature that can serve as the main information system of Poltekpar Palembang in student admission as an effort to fulfill the student admission quota.